Effect of Transfer Prindng Mechanism on Profitability of a Public and Private Sector Bank - Kumar, Babita; Banga, Gagandeep; Gupta , Ashima (Gyan Management Journal, 2008)
Transfer price in banks refers co the co c of funds transferred to and from head office and helps to arrive a a notional profit or loss of a branch before it is categorized as profit making or loss incurring branch. The research paper studies the Lransfer price mechanism of a public and private sector bank and understands the changes brought about by the transfer price mechanism in the profitability of the branches of the banks. One branch from each of the three categories i.e. urban, semi-urban and rural was selected from each bank. Thus, making the total sample size of 6 branches. Multiple transfer price mechanism was followed by State bank ·of Patiala and dual transfer price mechanism was followed by Bank of Rajasthan Ltd. Percentage change in operating profit and net result after applying transfer pricing rates was studied. It _was found that multiple transfer pricing has major impact